Glasgow prognostic score predicts efficacy and prognosis in patients with advanced non‐small cell lung cancer receiving EGFR‐TKI treatment. Issue 8 (3rd June 2020) - Kasahara, Norimitsu; Imai, Hisao; Naruse, Ichiro; Tsukagoshi, Yusuke; Kotake, Mie; Sunaga, Noriaki; Kaira, Kyoichi; Maeno, Toshitaka; Asao, Takayuki; Hisada, Takeshi
Abstract : Background: Lung cancer is the leading cause of cancer‐related deaths. Although epidermal growth factor receptor tyrosine kinase inhibitors (EGFR‐TKIs) are effective for advanced non‐small cell lung cancer (NSCLC) harboring EGFR mutations, some patients experience little or no response. The Glasgow prognostic score (GPS) is an inflammation‐related score based on C‐reactive protein (CRP) and albumin concentrations, and has prognostic value in various cancer settings. This study aimed to evaluate whether GPS could predict response of NSCLC to EGFR‐TKIs. Methods: This retrospective multicenter study evaluated patients with NSCLC harboring EGFR mutations who received EGFR‐TKI monotherapy from October 2006 to December 2016. GPS values were determined using CRP and albumin concentrations from before initiation of EGFR‐TKIs. The Kaplan‐Meier method and Cox proportional hazard models were used to evaluate progression‐free survival (PFS) and overall survival (OS). Results: In 214 patients, 141, 43, and two patients had GPS values of 0, 1, and 2, respectively. The GPS independently predicted the efficacy of EGFR‐TKIs; good GPS (0–1) conferred significantly better PFS (hazard ratio [HR]: 0.59, 95% confidence interval [CI]: 0.38–0.96, P = 0.03) and OS (HR: 0.56, 95% CI: 0.33–0.96, P = 0.03). Multivariate analysis confirmed that a good GPS (0–1) independently predicted good PFS and OS among patients who had PS of 0–1. Good GPS (0–1) independently predicted good OS among patients receiving treatment in first‐line settings. Conclusions: The GPS independently predicted the efficacy of EGFR‐TKIs for EGFR ‐mutated NSCLC; however, further studies are needed to validate our findings. Key points: Significant findings of the study: Glasgow prognostic score (GPS) independently predicted the efficacy of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR‐TKIs) treatment for EGFR ‐mutated NSCLC. What this study adds: The findings presented in this paper will help to identify patients who will be expected to experience limited or no response to EGFR‐TKI treatment by using GPS.